[PP.19.14] THE BODY SHAPE INDEX IS ASSOCIATED WITH THE VASCULAR STRUCTURE AND FUNCTION IN CAUCASIAN ADULTS. MARK STUDY. (September 2017) - Gomez-Sanchez, L.; Garcia-Ortiz, L.; Patino-Alonso, M.C.; Recio-Rodriguez, J.I.; Rigo, F.; Marti, R.; Agudo-Conde, C.; Gomez-Sanchez, M.; Gonzalez-Sanchez, J.; Rodriguez-Sanchez, E.; Maderuelo-Fernandez, J.A.; Ramos, R.; et al.
Abstract : Objective: The body shape index (ABSI)—has been introduced as a marker of the association between body composition and all-cause mortality. However, until now, associations between ABSI and vascular structure and function have not been evaluated. The aim of this study was to investigate the association of ABSI with the vascular structure and function in Caucasian adults with intermediate cardiovascular risk. Design and method: Design: We performed a cross-sectional study. Subjects/Methods: This study analyzed 2354 subjects, aged 35 to 74 years (mean, 61.4 ± 7.7 years), 61.9% males, enrolled into the MARK study. ABSI was calculated by ABSI = WC (m)/body mass index (BMI)2/3 x height (m)1/2. Vascular function was assessed by measuring cardio-ankle vascular index (CAVI) with the VaSera device and brachial ankle pulse wave velocity (baPWV) by using a validated equation. Vascular structure was assessed by measuring carotid intima-media thickness (IMT) by ultrasonography. Results: Mean values of ABSI (0.083 ± 0.001), CAVI (8.8 ± 1.2), and IMT (0.738 ± 0.093), were higher in males. ABSI was positively associated with CAVI, baPWV and with average mean IMT after adjusting for confounders. Thus, for each unit increase in ABSI, CAVI increased by 0.12 units, baPWV by 0.21 m/sec, and IMT by 0.037 mm. In the logistic regression analysis, the OR of the ASBI was >1 for high CAVI > 9, baPWV > 15 m/sec and IMT > 0.90 mm, in the overall subjest, and by sex and age (>62, <62 years), after adjusting for confounders. Conclusions: ABSI shows a positive association with vascular structure and function, which is independent of BMI and other confounders that may influence weight and fat mass distribution in Caucasian subjects at intermediate cardiovascular risk.